Souvenirs of Madame Vigée Le Brun, Volume 2 - Vigée-Lebrun, Louise-Elisabeth 1755-1842 (Cambridge University Press, 2016)
The most accomplished female painter of her age, Élisabeth Vigée-Lebrun (1755–1842) is best remembered for her many portraits of Queen Marie Antoinette of France. Her two-volume autobiography was published in France in 1835–7, and this English version (of which the translator is unknown) in 1879. It begins with a series of letters to a Russian friend, Princess Kourakin, describing her family and early life, her artistic training, and her rise to the position of portraitist to the queen. The letters end with the Revolution and Vigée-Lebrun's flight abroad: the 'souvenirs' which follow describe her years of exile and her eventual return to France. Throughout her life, she supported herself and her family by her painting. Volume 2 recounts her extended stay in Russia, where she painted many of the aristocracy, a brief return to Paris, a visit to England, and her final return to France
Keywords: Vigée-Lebrun, Louise-Elisabeth / 1755-1842; Vigée-Lebrun, Louise-Elisabeth -- 1755-1842; Painters / France / Biography; Kunst; Bildnis; Autobiografie; Schrifttum; Frankreich; Europa; Biografie